Sulfonylative and Azidosulfonylative Cyclizations by Visible‐Light‐Photosensitization of Sulfonyl Azides in THF. Issue 69 (16th November 2017) - Zhu, Shaoqun; Pathigoolla, Atchutarao; Lowe, Grace; Walsh, Darren A.; Cooper, Mick; Lewis, William; Lam, Hon Wai
Abstract: The generation of sulfonyl radicals from sulfonyl azides using visible light and a photoactive iridium complex in THF is described. This process was used to promote sulfonylative and azidosulfonylative cyclizations of enynes to give several classes of highly functionalized heterocycles. The use of THF as the solvent is critical for successful reactions. The proposed mechanism of radical initiation involves the photosensitized formation of a triplet sulfonyl nitrene, which abstracts a hydrogen atom from THF to give a tetrahydrofuran‐2‐yl radical, which then reacts with the sulfonyl azide to generate the sulfonyl radical. Abstract : The generation of sulfonyl radicals from sulfonyl azides using visible light photocatalysis is described. This process was used to promote azidosulfonylative and sulfonylative cyclizations of various enynes to give several classes of highly functionalized heterocycles. The use of THF as the solvent is critical for successful reactions.